THE ISLAM-ORIENTED HOUSE STRUCTURE IN KANO: A VANISHING HERITAGE IN MODERN CITY COMPOSITION - Yahya, Ahmad (Journal of Islamic Architecture, 2012)
he debut of colonialism along with the consequent de facto supremacy of the Western world did not onlynegatively impact on the economy and polity of the Muslim world. It has also, to some reasonable extent,polluted the social system, particularly the structure and form of cities. Human scale is gradually diminishingas a yardstick for construction and is being replaced by a mathematical one. Collectivism, which used tocharacterize Muslims' social set-up, is now being over-shadowed by stark individualism. The Islamic socialvalues which used to be the binding force that held Muslims together are now being crushed by moralrelativity. The situation becomes so chronic that many people begin to assume that Islam has a very negligiblerole to play in the formation and construction of modern cities. Kano, a predominantly Muslim state in NorthWesternNigeria, inherited a thousand year-old Islam-oriented building architecture which made it a modelIslamic city in pre-colonial Africa. Of special reference is the residential structure which no doubt reflectsIslamic culture. Unfortunately, this age-old heritage is now being pushed to the brink of extinction by thealmighty modern architecture. This paper explores the Islamic in the Kano traditional residential structure andattempts to comparatively bring into light the extent to which it is diminishing in the modern buildingarchitecture. The paper suggests blending the two for a peaceful and harmonious co-existence.Â  Â